2023
DOI: 10.1038/s41534-023-00706-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum error correction with gauge symmetries

Abstract: Quantum simulations of lattice gauge theories (LGTs) are often formulated on an enlarged Hilbert space containing both physical and unphysical sectors in order to retain a local Hamiltonian. We provide simple fault-tolerant procedures that exploit such redundancy by combining a phase flip error correction code with the Gauss’ law constraint to correct one-qubit errors for a $${{\mathbb{Z}}}_{2}$$ Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…After N gauge constraints (stabilizer conditions) are imposed, the gaugeinvariant subspace (code space) has dimension 2 N , which matches the dimension of the logical fermions. It has been shown that gauge constraints can be utilized for error correction [54], and code distances can be studied for these stabilizer codes. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…After N gauge constraints (stabilizer conditions) are imposed, the gaugeinvariant subspace (code space) has dimension 2 N , which matches the dimension of the logical fermions. It has been shown that gauge constraints can be utilized for error correction [54], and code distances can be studied for these stabilizer codes. Ref.…”
Section: Introductionmentioning
confidence: 99%